2016
DOI: 10.1038/srep37000
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Microstructure Fabrication: Polyelectrolyte Complexes vs Polyelectrolyte Multilayers

Abstract: Polyelectrolyte complexes (PEC) are formed by mixing the solutions of oppositely charged polyelectrolytes, which were hitherto deemed “impossible” to process, since they are infusible and brittle when dry. Here, we describe the process of fabricating free-standing micro-patterned PEC films containing array of hollow or filled microchambers by one-step casting with small applied pressure and a PDMS mould. These structures are compared with polyelectrolyte multilayers (PEM) thin films having array of hollow micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…However, recent work has demonstrated that salt can be used to plasticize PECs to enable processing. 4148 To date, PECs have been extruded into single fibers, 44,49 electrospun into fiber meshes, 41,42 processed into free-standing microchambers, 46 spin-coated into films, 43 cast into films, 45 and 3D-printed into material forms. 50,51…”
Section: Introductionmentioning
confidence: 99%
“…However, recent work has demonstrated that salt can be used to plasticize PECs to enable processing. 4148 To date, PECs have been extruded into single fibers, 44,49 electrospun into fiber meshes, 41,42 processed into free-standing microchambers, 46 spin-coated into films, 43 cast into films, 45 and 3D-printed into material forms. 50,51…”
Section: Introductionmentioning
confidence: 99%
“…Recently drop‐casting was also suggested as a more readily available alternative for making the templates . Microchambers may be fabricated via one‐step casting of a polyelectrolyte complex onto, or LbL assembly of PEMs on a template . The latter approach requires significantly longer time but allows layered structures which is specifically advantageous for effective stress transfer in PEGOM nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Enhanced mechanical properties of PEGOM films could be specifically advantageous for making 3D structures, e.g., an array of microchambers developed recently . Potential applications of these structures include micropackaging of drugs, or sensors for rapid diagnostics of biological fluids, where resilience of the microchambers toward external stresses is required to avoid accidental burst release, the event that could be catastrophic.…”
Section: Introductionmentioning
confidence: 99%
“…Combining soft‐lithography with LbL can occur in different ways: printing, molding or embossing the PDMS structure on the surface of the multilayer film material or constructing an LbL‐based system above the patterned PDMS substrate. For instance, polyelectrolyte multilayers presenting an array of microgrooves were already produced by layer‐by‐layer assembly on patterned PDMS molds and compared with polyelectrolyte complexes prepared in the same conditions …”
Section: Fabrication Techniques To Obtain Micro‐and Nanopatterned Surmentioning
confidence: 99%